2000
DOI: 10.1046/j.1365-2648.2000.01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Disposition towards critical thinking: a study of Chinese undergraduate nursing students

Abstract: The purpose of this study was to explore empirically whether undergraduate nursing students at a selected university in Hong Kong display a disposition towards critical thinking. The California Critical Thinking Dispositions Inventory (CCTDI) was used to measure the key theoretical aspects of the overall dispositional dimension of critical thinking. A cross-sectional descriptive design was used to examine 122 Chinese students who were completing their 1st, 2nd and 3rd year of a university baccalaureate nursing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
67
3
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 10 publications
22
67
3
4
Order By: Relevance
“…Shin (1998) investigated critical thinking of undergraduate and graduate nursing students and observed significant differences between critical thinking levels of nursing students at different level of education. Ip et al (2000) assessed the critical thinking trends of 122 undergraduate nursing students in Hong Kong and reported significant differences in critical thinking scores of the first-year students. Walsh and Hardy (1999) compared the critical thinking scores of university students at different majors.…”
Section: Discussionmentioning
confidence: 99%
“…Shin (1998) investigated critical thinking of undergraduate and graduate nursing students and observed significant differences between critical thinking levels of nursing students at different level of education. Ip et al (2000) assessed the critical thinking trends of 122 undergraduate nursing students in Hong Kong and reported significant differences in critical thinking scores of the first-year students. Walsh and Hardy (1999) compared the critical thinking scores of university students at different majors.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the term critical thinking is widely used in nursing literature, adopted in clinical practice (Koch, 1997), in educational programmes (Ribbons, 1998, Loving, 2000 and has been the focus of research projects (Girot, 2000, Ip et al, 2000, Daly, 2001). In the US, Loving, (2000) used Paul's model (Paul, 1995) as a framework for the integration of critical thinking skills in nursing courses.…”
Section: Instructional Methods To Develop Critical Thinking In Nurse mentioning
confidence: 99%
“…A study by Agbedia et al (2008) on the disposition towards critical thinking of nursing students from Nigeria showed that the respondents were low on scores on truth seeking and opens mindedness. The study by Ip et al (2000) explored the disposition towards critical thinking of Chinese students; Tiwari et al (2003) went a step further to compare the disposition towards critical thinking of Chinese and Australia nursing students. The result showed that Australian nursing students were better thinker than the Chinese.…”
Section: Issues Influencing the Use Of Critically Thinking In Nursingmentioning
confidence: 99%